2015
DOI: 10.1002/jemt.22541
|View full text |Cite
|
Sign up to set email alerts
|

The osteogenic effects of swimming on bone mass, strength, and microarchitecture in rats with unloading-induced bone loss

Abstract: The effect of nonweight-bearing exercise on osteoporotic bones remains controversial and inconclusive. The purpose of this study was to evaluate the effects of swimming on osteoporotic tibias of rats submitted to hindlimb suspension. Initially, 20 Wistar rats were used to confirm a significant bone loss following 21 days of unloading. Thirty rats were then divided into 3 groups and followed during 51 days: CON (nonsuspended rats), S + WB (suspended rats for 21 days and then released for regular weight-bearing)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…The distance between the points was 25 mm, and a pre-load of 5 N for 30 seconds was used based on the recommendations found in [22][23][24].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…The distance between the points was 25 mm, and a pre-load of 5 N for 30 seconds was used based on the recommendations found in [22][23][24].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…In young and mature rodents, treadmill/voluntary wheel‐running exercise improved BMD, bone microarchitecture, and biomechanical strength, and was protective against estrogen‐deficiency‐induced bone loss . Non‐weight‐bearing‐swimming exercise also prevented bone loss associated with ovariectomy or hindlimb suspension . In the following study, we investigated the effect of weight‐bearing (voluntary wheel‐running) and non‐weight‐bearing‐ (swimming) physical activity on musculoskeletal mass and strength in wild type (WT) and homozygous OI murine ( oim/oim ) mice.…”
Section: Introductionmentioning
confidence: 99%
“…(19,20) Non-weightbearing-swimming exercise also prevented bone loss associated with ovariectomy or hindlimb suspension. (21)(22)(23) In the following study, we investigated the effect of weight-bearing (voluntary wheel-running) and non-weight-bearing-(swimming) physical activity on musculoskeletal mass and strength in wild type (WT) and homozygous OI murine (oim/oim) mice. Gentry and colleagues were the first to identify an intrinsic muscle pathology in OI by demonstrating that oim/oim mice have reduced specific muscle contractile function (described as the peak tetanic force normalized to myofiber cross sectional area) as compared with WT littermates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exercise promotes metabolic and hormonal alterations that also stimulate the synthesis of calcium in bone tissue [15][16][17] . Thus, the aquatic exercise-induced increase in mineral density (ET8 group) could be explained by the mechanical stress caused by the tendon traction on the bones during muscle contraction, together with the metabolic and hormonal alterations caused by exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that this type of exercise can be used in conditions of severe loss of bone mass as a method of treatment, especially in cases with a high-risk of fractures, as the reduced impact on the bones from this exercise modality makes practitioners less susceptible to bone fractures 12,17 . With respect to the anaerobic training, it presented higher osteogenic potential than aerobic training (swimming) since after just four weeks, it was able to significantly increase BMD with respect to the aerobic swimming training groups (ET4) and the group without training (BL), and the same occurred with concurrent training.…”
Section: Discussionmentioning
confidence: 99%